2021
DOI: 10.1097/jxx.0000000000000672
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic journey in adults with hypermobile Ehlers–Danlos syndrome and hypermobility spectrum disorders

Abstract: Background: Researchers have identified lengthy diagnosis delays in patients with hypermobile Ehlers-Danlos syndrome and hypermobility spectrum disorders (hEDS/HSD), but the reason for these delays is unclear.Objective: This review seeks to synthesize the existing qualitative research about hEDS/HSD to understand the reasons for diagnosis delay.Data sources: We searched PubMed, Scopus, CINAHL, Google Scholar, and Dissertations and Theses databases for all qualitative studies about hEDS/HSD that mentioned the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Most participants ( n = 370; 80%) indicated their primary care provider (PCP) was involved in management of their condition as they are perhaps the best‐suited HCP to be the main point of contact for care coordination and referrals. However, previous literature has shown that PCPs are not uniformly aware of hEDS and may benefit from continuing education on the topic as they are often the first HCP to be notified of symptoms by the patient (Anderson & Lane, 2021). PCPs also see a greater frequency of patients with hEDS than those who present to specialists through the recognition of specific symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most participants ( n = 370; 80%) indicated their primary care provider (PCP) was involved in management of their condition as they are perhaps the best‐suited HCP to be the main point of contact for care coordination and referrals. However, previous literature has shown that PCPs are not uniformly aware of hEDS and may benefit from continuing education on the topic as they are often the first HCP to be notified of symptoms by the patient (Anderson & Lane, 2021). PCPs also see a greater frequency of patients with hEDS than those who present to specialists through the recognition of specific symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pain can be a contributor to the psychological burden of disease (Hershenfeld et al, 2016; Pasquini et al, 2014) but it is yet unclear if psychological disorders are a part of the syndrome or develop as a consequence of the condition's debilitating symptoms, patients' diagnostic journeys, previous poor experiences with HCPs, or a combination of these and other factors. Based on the reported experiences of patients with hEDS, there is a clear need for increased awareness and education of HCPs on the spectrum of the condition and its multifaceted nature (Anderson & Lane, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The predominant clinical feature of joint hypermobility, assessed using the Beighton score, is used to guide the identification process, but could be affected by the regression of the condition, and replaced with joint stiffness, which further complicates the diagnostic process. A recent review related the diagnostic delay of hEDS/HSD to the lack of a confirmatory diagnostic approach ( 17 ). Ultimately, there is a need for a more objective diagnostic procedure to improve the subjectivity of existing diagnostic approaches.…”
Section: Introductionmentioning
confidence: 99%